2018
DOI: 10.1108/compel-12-2016-0521
|View full text |Cite
|
Sign up to set email alerts
|

A novel MRTD model for signal integrity analysis of resistive driven coupled copper interconnects

Abstract: Purpose This paper aims to model the coupled on-chip Copper (Cu) interconnects by using the multiresolution time-domain (MRTD) method. Design/methodology/approach The proposed model is a wavelet-based numerical method for analyzing signal integrity and propagation delay of coupled on-chip interconnects. Moreover, the dependency of crosstalk noise and delay on coupling parasitics (L12, C12) are analyzed. Findings The proposed MRTD method captures the behaviour of propagation delay and peak crosstalk noise o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Features and improved precision with SPICE, relative to the FDTD model. Rebelli et al [20,21] suggested the MRTD approach to evaluate the signal integrity of coupled Copper interconnect driven by linear resistive and a nonlinear CMOS dependent on the Daubechies scaling function at four extinct moments. and also, Rebelli et al [22] applied the MRTD approach driven to nonlinear CMOS using the nth-power law model to evaluate crosstalk noises in coupled on-chip interconnects.…”
mentioning
confidence: 99%
“…Features and improved precision with SPICE, relative to the FDTD model. Rebelli et al [20,21] suggested the MRTD approach to evaluate the signal integrity of coupled Copper interconnect driven by linear resistive and a nonlinear CMOS dependent on the Daubechies scaling function at four extinct moments. and also, Rebelli et al [22] applied the MRTD approach driven to nonlinear CMOS using the nth-power law model to evaluate crosstalk noises in coupled on-chip interconnects.…”
mentioning
confidence: 99%
“…Tong et al 23,24 proposed the MRTD model for transient analysis of two-conductor transmissions lines which outperformed the traditional FDTD in terms of numerical dispersion and accuracy when compared to SPICE. Rebelli et al 25,26 suggested that the MRTD approach is used to evaluate the signal integrity issues of a coupled copper interconnect driven by a linear resistive and a nonlinear CMOS dependent on the Daubechies scaling function at four extinct moments and also Rebelli et al 27 applied the MRTD approach driven to non-linear CMOS employing the nth power-law model to evaluate crosstalk noises in mutually coupled Multiwalled Carbon Nanotube interconnects. The crosstalk effects of SWCNT bundle interconnects have been investigated using the FDTD method with a resistive driver.…”
mentioning
confidence: 99%